Housing Young People. - Forrest, Ray (Housing and society series., 2012)
Young People and Housing brings together new research exploring the economic, social, and cultural challenges that face young people in search of permanent housing. Featuring international case studies from Asia, Europe, and Australia, Young People and Housing is a collection of groundbreaking work from leading scholars in housing policy. Younger generations across a wide range of societies face increasing difficulties in gaining access to housing. Housing occupies a pivotal position in the transition from parental dependence to adult independence. Delayed independence has significant implicati.